Atlas of human rights : mapping violations of freedom around the globe - Fagan, Andrew, 1966- (Berkeley : University of California Press, 2010)
This timely atlas reveals human rights inequities from nation to nation and the consequences of these violations worldwide.
Foreword / Clive Stafford Smith -- State, identity & citizenship. Political rights ; Citizenship ; Wealth & inequality ; Quality of life ; Health -- Judicial violations & legal restrictions. Torture ; Arbitrary detention ; Capital punishment ; Policing -- Freedom of expression & censorship. Freedom of speech ; Communications censorship ; Assembly & association -- Conflict & migration. Genocide ; War & armed conflict ; Arms trade ; Terrorism ; UN peacekeeping ; Refugees, IDPs & stateless -- Discrimination. Religious freedom ; Minorities ; Racism ; Disabilities & mental health ; Sexual freedom -- Women's rights. Women's civil rights ; Domestic violence ; Rape ; Right to choose ; Female genital mutilation ; Sex slavery -- Children's rights. Child labour ; Child soldiers ; Education ; Child morality & health -- Country profiles & world data.
Includes bibliographical references and index.
Keywords: Human rights; Human rights